To Splice or to Transcribe: SKIP-Mediated Environmental Fitness and Development in Plants - Cao, Ying; Ma, Ligeng (Frontiers in Plant Science, 2019)
Gene expression in eukaryotes is controlled at multiple levels, including transcriptional and post-transcriptional levels. The transcriptional regulation of gene expression is complex and includes the regulation of the initiation and elongation phases of transcription. Meanwhile, the post-transcriptional regulation of gene expression includes precursor messenger RNA (pre-mRNA) splicing, 5′ capping, and 3′ polyadenylation. Among these events, pre-mRNA splicing, conducted by the spliceosome, plays a key role in the regulation of gene expression, and the efficiency and precision of pre-mRNA splicing are critical for gene function. Ski-interacting protein (SKIP) is an evolutionarily conserved protein from yeast to humans. In plants, SKIP is a bifunctional regulator that works as a splicing factor as part of the spliceosome and as a transcriptional regulator via interactions with the transcriptional regulatory complex. Here, we review how the functions of SKIP as a splicing factor and a transcriptional regulator affect environmental fitness and development in plants.